Study on the Factors Influencing College Teachers to Buy a Car in Krishnagiri District, Tamilnadu - Priya, N; Ravi, A. (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
It is evident that our country is growing in a excellent manner. As equal as to the developed nation, India is equally contributing in the car market and several companies came in to India and challenging with Indian companies in car segment. Automobile industry is one of the major area in contributing tremendous growth in GDP. No doubt that car is a essential product for all income group and the college teachers are highly targeted customers for small car segment. The distributors are attracting the middle income group for selling their small cars through various attractive scheme in Krishnagiri district. Most of the teachers are from rural background but having family support for improving their life style. Having a car for a teacher, who is working in either private or Government College is a prestige issue and approaching the dealers for selecting their choice in car segments. According to the environmental condition and stressful traffic system, the road condition in rural areas are not improved for safety car driving. In India it is a slogan of any individual to have a house, a car and attractive life style with living place.